Let u be (18/(-10))/((-57)/95). Solve -4*x + 1 = -u for x.
1
Let f(m) be the third derivative of m5⁄20 - m4⁄12 + 6*m**2. Let q be f(-1). Solve -h - 4 = -q*h for h.
1
Let c(z) be the first derivative of z3⁄3 - 5*z2⁄2 - 2*z - 2. Let t be c(6). Let h = -1 + t. Solve 2*x = -h*x + 25 for x.
5
Let n be 2(-3)/6-2. Solve -n*i + 1 + 1 = 0 for i.
1
Suppose -2*o + 5 = -1. Let c be (-2 + 3)*1*o. Solve -c*v = 2*v + 10 for v.
-2
Suppose -125*b = -127*b + 4. Solve 0 = 2*a + b for a.
-1
Suppose 0 = 3*y + 4*v - 1 - 3, -5*y = 5*v - 15. Solve -3*c + y*c = 15 for c.
3
Let h(g) = g3 - 9*g2 + 7*g - 10. Let d be h(8). Let l be d/(-1)*1⁄2. Solve 0 = -o - 2*o - l for o.
-3
Let o© = c3 + 12*c2 + 10*c - 8. Let s be o(-11). Solve -x + s*x = -2 for x.
-1
Suppose -3*u + 0*t = 3*t - 6, 0 = -3*u - 4*t + 4. Suppose -11*g + 10 = -6g. Let f be (-1 - 7)(-15)/12. Solve -f = g*j - u*j for j.
5